2011
DOI: 10.1194/jlr.m010082
|View full text |Cite
|
Sign up to set email alerts
|

The mPlrp2 and mClps genes are involved in the hydrolysis of retinyl esters in the mouse liver

Abstract: This article is available online at http://www.jlr.org version to active-form retinoic acid, which interacts with the nuclear receptors of the RXR and RAR families, functioning as hormone-activated factors in the regulation of the expression of multiple genes ( 1, 2 ). Also, vitamin A mediates vision cycles through its metabolite, 11-cis retinaldehyde, which is the active chromophore in rhodopsin ( 3, 4 ). Most of the retinoids in the body are accounted for by the retinyl esters stored in the liver ( 5, 6 ). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…In the meantime, SAM is one of the substrates for DNMTs, high levels of SAM increase the activity of DNMTs, which is reflected in the global methylation experiment. Apart from DNA methylation, Hcy is associated with histone methylation, which alters the expression of remodeling genes 34 . Our study showed an increase in H3K27me3 on CFTR promoter and the expression of EZH2 in CBS +/- mice.…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime, SAM is one of the substrates for DNMTs, high levels of SAM increase the activity of DNMTs, which is reflected in the global methylation experiment. Apart from DNA methylation, Hcy is associated with histone methylation, which alters the expression of remodeling genes 34 . Our study showed an increase in H3K27me3 on CFTR promoter and the expression of EZH2 in CBS +/- mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was also reported that expression of mutant PNPLA3 in HSCs leads to the depletion of retinol, but higher lipid droplet content was accompanied by increased release of proinflammatory cytokines, suggesting a role for this mutation in HSC activation [46]. Other enzymes probably involved in retinol mobilization are lipoprotein lipase (LPL), pancreatic-related protein 2 (mPlrp2), and procolipase (mClps), which were all reported to be significantly increased in activated HSCs [47,48]. Interestingly, in rat HSCs, seven days after activation of the culture by plating on a plastic surface, retinyl loss was not accompanied by triglyceride decrease [49].…”
Section: Hepatic Stellate Cellsmentioning
confidence: 99%
“…However, few details of how this is achieved are known, e.g., it is unknown how retinol gets in and out of HSC and which (molecular) signals control this. Mobilization of retinol from lipid droplets in HSC is catalyzed by REHs, and several enzymes are implicated in this process, including adipose triglyceride lipase (ATGL/PNPLA2) [ 44 ], patatin-like phospholipase domain-containing 3 (PNPLA3) [ 44 , 45 , 46 ], and hormone-sensitive lipase (HSL) [ 47 , 48 ]. Interestingly, genetic studies have identified the PNPLA3-I148M variant as a prominent genetic factor associated with NAFLD, and even more prominently with disease progression within NAFLD to NASH and NASH-associated cirrhosis [ 49 , 50 , 51 ].…”
Section: Vitamin a Uptake Storage And Metabolismmentioning
confidence: 99%